2008
DOI: 10.1537/ase.070130
|View full text |Cite
|
Sign up to set email alerts
|

Growth of height and leg length of children in Beijing and Xilinhot, China

Abstract: A number of papers on the growth of Chinese children have been published in local journals in China in the Chinese language. However, we noticed that height and weight are the main focus of these studies. Because leg length relative to height is of interest in human biology, the current study focuses on the growth of this proportion. Two groups of Chinese children were investigated: 587 boys and 625 girls in Beijing in 1997 aged 6-18 years, and 579 boys and 615 girls in Xilinhot, Inner Mongolia, in 2005 aged 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In view of differences in socio-economic conditions between urban and rural communities in China [93,94,9699], differences between Han people and minority groups [91,93, 96,97] and ethnic differences in body build [99101], the present prediction equations may not fit all East Asian ethnic groups equally well. Whereas post-war improvements in socio-economic conditions in Japan led to increased height driven by growth of leg length [102], with the exception of Chinese girls in Beijing [103], there is no obvious secular trend in the leg length/height ratio [100,103,104], suggesting that as people grow taller lung volumes increase proportionately. However, more information is required about pulmonary function in other ethnic groups, including ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…In view of differences in socio-economic conditions between urban and rural communities in China [93,94,9699], differences between Han people and minority groups [91,93, 96,97] and ethnic differences in body build [99101], the present prediction equations may not fit all East Asian ethnic groups equally well. Whereas post-war improvements in socio-economic conditions in Japan led to increased height driven by growth of leg length [102], with the exception of Chinese girls in Beijing [103], there is no obvious secular trend in the leg length/height ratio [100,103,104], suggesting that as people grow taller lung volumes increase proportionately. However, more information is required about pulmonary function in other ethnic groups, including ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is suggestive evidence that parental phenotype and prenatal environment might affect the sexes differently (Pembrey et al, 2005; Anderson et al, 2006; Thone-Reineke et al, 2006; Chen et al, 2012; Aiken and Ozanne, 2013), reported patterns are rarely tested statistically. Such differences might be predicted theoretically since males are thought to place a greater demand on maternal physiology (Stinson, 1985) due to their faster growth and larger size (Catalano et al, 1995; Hindmarsh et al, 2002; Melamed et al, 2013), and to be more sensitive to early growth disturbance (Stini, 1969; Stinson, 1985; Kuh et al, 1991; Wamani et al, 2007; Ashizawa et al, 2008; Decaro et al, 2010). However, we found no evidence of such a contrast in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 29 In sample populations in China, there are considerable differences in socioeconomic conditions between urban and rural areas 30 31 and ethnic differences in body builds. 32 33 Since certain traits are not shared across ethnic groups and regions, the development of separate spirometric equations for each ethnicity and country is needed. Nevertheless, the work from the GLI has advantages in certain situations.…”
Section: Discussionmentioning
confidence: 99%